Acute stress reduces wound-induced activation of microbicidal potential of ex vivo isolated human monocyte-derived macrophages. - Ulrike Kuebler; Petra H Wirtz; Miho Sakai; Andreas Stemmer; Ulrike Ehlert (PLoS ONE, 2013)
BACKGROUND: Psychological stress delays wound healing but the precise underlying mechanisms are unclear. Macrophages play an important role in wound healing, in particular by killing microbes. We hypothesized that (a) acute psychological stress reduces wound-induced activation of microbicidal potential of human monocyte-derived macrophages (HMDM), and (b) that these reductions are modulated by stress hormone release. METHODS: Fourty-one healthy men (mean age 35 ± 13 years) were randomly assigned to either a stress or stress-control group. While the stress group underwent a standardized short-term psychological stress task after catheter-induced wound infliction, stress-controls did not. Catheter insertion was controlled. Assessing the microbicidal potential, we investigated PMA-activated superoxide anion production by HMDM immediately before and 1, 10 and 60 min after stress/rest. Moreover, plasma norepinephrine and epinephrine and salivary cortisol were repeatedly measured. In subsequent in vitro studies, whole blood was incubated with norepinephrine in the presence or absence of phentolamine (norepinephrine blocker) before assessing HMDM microbicidal potential. RESULTS: Compared with stress-controls, HMDM of the stressed subjects displayed decreased superoxide anion-responses after stress (p's <.05). Higher plasma norepinephrine levels statistically mediated lower amounts of superoxide anion-responses (indirect effect 95% CI: 4.14-44.72). Norepinephrine-treated HMDM showed reduced superoxide anion-production (p<.001). This effect was blocked by prior incubation with phentolamine. CONCLUSIONS: Our results suggest that acute psychological stress reduces wound-induced activation of microbicidal potential of HMDM and that this reduction is mediated by norepinephrine. This might have implications for stress-induced impairment in wound healing.